STATEMENT OF INTENT between Faculty of Mechanical Engineering Universiti Teknologi Malaysia and Faculty of Engineering University of Liverpool United Kingdom - Md. Nor Musa; Ieuan, Owen; University of Liverpool United Kingdom; Universiti Teknologi Malaysia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2006)
PRZSL